African geoxyles evolved in response to fire; frost came later - Lamont, Byron; He, Tianhua; Pausas, J. (Springer Netherlands, 2017)
It has been proposed in separate studies that fire or frost were the critical selective agents in the evolution of subshrub geoxyles (SGs) in African subtropical grasslands. We attempt to resolve this controversy by examining the evolution of SGs among the entire genus Protea that is widespread throughout southern/central Africa. We show that SGs are not confined to grasslands but occur in a wide range of non-forest vegetation types, including mediterranean shrublands. SG proteas arose 1–11 million years ago but their multiple origins among other geoxyles, confounded by strong intraspecific variability among grassland species, makes it impossible to identify the ancestral growth form. We conclude that the evolutionary history of SG proteas has occurred under lightning-prone conditions that promoted fire and were essentially frost-free; exposure to frost has been limited to certain elevated locations in more recent times. This is supported by many SGs having pyrogenic flowering and lack of seed storage among grassland species.